Pengaruh Ukuran Partikel dan Perekat Taipoka Terhadap Sifat Biopelet dari Limbah Serbuk Gergajian - Permatasari, Dea; Rahmawati, Winda; Haryanto, Agus (Jurnal Agricultural Biosystem Engineering, 2023)
Biopellets from sawdust can be an alternative solution for dealing with sawn waste. This study aims to determine the effect of sawdust particle size and adhesive content on the characteristics of the resulting pellets. The study was conducted in a completely randomized two-factor design. The first factor was particle size which consisted of 4 levels, namely fine, medium, coarse, and mixed. The second factor was the tapioca flour as adhesive material consisted of 3 levels, namely 10%, 15% and 20%. Pellets were made using a single die with a diameter of 8 mm which was pressed using a hydraulic jack with a capacity of 5 tons. Parameters to be measured included moisture content, calorific value, ash content, density, and pellet strength (durability index). The raw material of wood sawdust has physico-chemical characteristics including 9.4% moisture content, 6.04% ash content, and 18.58 MJ/kg calorific value. The results showed that pellets had specific gravity between 1.018-1.086 kg/L, moisture content between 13.26-14.42%, and ash content between 0.98-2.42%. The resulting pellets have an average strength of more than 99%. Keywords:  Biopellet, Calorific Value, Pellet Characteristics, Wood Sawdust.